Rola modlitwy w życiu syryjskich mnichów według Teodoreta z Cyru - Skotnicka, Katarzyna (Vox Patrum, 2014)
Prayer was a basic goal of the lives of Christian monks. Historia religiosa by Theodoretus of Cyrus conveys a lot of valuable information on the subject of prayer of Syrian ascetics. The bishop of Cyrus used the notion of prayed to refer to any kind of requests and begging or thanksgiving and admiration. Theodoretus recorded particularly numerous examples of recoveries, which occurred by dint of intercessive prayer of ascetics. Monks prayed at different times of a day and in various postures (standing, lying or kneeling), they were also familiar with many kinds of prayer and addressed God with varied intentions. Historia religiosa informs us as well about gestures that accompanied prayers, such as bows, raising arms and eyes to the sky and places where it could be said. An important issue discussed by Theodoretus was the time of praying. In Historia religiosa we can find references to the ideal of incessant prayer and to morning and evening prayers typical for Christians. The aim of prayer was to help ascetics control their bodily needs, it drew the mind of an ascetic towards God, tearing them, at the same time, from worldly issues. Prayer was also a reflection of monk’s faith, since through it, they worshipped God, referred to him their requests and thanksgiving.